Different strategies of 25OH vitamin D supplementation in HIV-positive subjects. (October 2014) - Falasca, Katia; Ucciferri, Claudio; Di Nicola, Marta; Vignale, Francesca; Di Biase, Jessica; Vecchiet, Jacopo
Summary: A high incidence of 25OH vitamin D deficiency has been observed in HIV-infected subjects. The objective of this study was to evaluate the effect of cholecalciferol administration on serum 25OH vitamin D levels in HIV-infected patients. This prospective cohort study included 153 HIV-positive subjects; 47 were treated with 300, 000 IU intramuscular cholecalciferol, 67 with 25, 000 IU oral cholecalciferol monthly, while the remaining 39 did not receive any treatment. The group treated orally had an increase of serum 25OH vitamin D concentration, changing from 15.7 ± 12.2 ng/mL to 27.4 ± 11.6 ng/mL after 10 months (T10). The group treated with intramuscular supplementation had an improvement, changing from 18.5 ± 10.5 ng/mL to 32.9.0 ± 12.2 ng/mL at T10. One-way repeated measures analysis of variance indicated a significant difference for 25OH vitamin D variation ( p  = 0.002) among the three groups. A significant effect of time ( p  < 0.001) and group × time interaction ( p  < 0.001) was found: at T10, 25OH vitamin D values were significantly higher in the oral and intramuscular groups with respect to the control group. Our findings showed that the supplementation with cholecalciferol in patients with HIV-infection improved 25OH vitamin D serum levels, and suggest that the two types of administration are equivalent, but are insufficient for severe forms of hypovitaminosis.